How to publish in a peer-reviewed indexed journal and the importance of single author articles - Quayum, Mohammad Abdul (2015)
To explain the importance of research and publication in the academia, and to outline the ways of writing scholarly articles and getting them published in Scopus or ISI indexed journals. Also to elaborate on why and how single author papers at important in the humanities and the social sciences.